Layanan Pembelajaran Untuk Anak Berkebutuhan Khusus Di SDN Menur Pumpungan IV Dalam Perspektif Collaborative Governance - Melda Eka Fernia (Jurnal Relasi Publik, 2024)
This research aims to: (1) find out and understand how the collaboration between the government, teachers and parents in the implementation of special education for children with special needs at SDN Menur Pumpungan IV, (2) to know and understand what learning services are implemented in the process teaching children with special needs at the SDN Menur Pumpungan IV. The type of research used is qualitative descriptive research. Research subjects included class teachers, school principals, and classmates of children with special needs at SDN Menur Pumpungan IV. The method used in this research is the case study method. Data collection uses observation and interview techniques. The data obtained was then analyzed using the interactive model from Miles and Huberman with the steps of data condensation, data display, and conclusion drawing. The results of the show that at SDN Menur Pumpungan IV there are two students with special needs who have a background of slow learners and hyperactivity disorder. The class teacher who teachesthe two students always differentiates learning for students with special need from other normal student.